Design and Fabrication of a Semi- Automatic Shoe Polishing Machine for Small Scale Business - Taiwo Semiu Amosun; Shedrak E. Azike (R.E.M. (Rekayasa Energi Manufaktur) Jurnal, 2022)
Shoe is generally made from leather which requires extreme care and regular polishing to maintain its shiny appearance. This work attempts to develop a semi-automatic shoe polishing machine for small scale enterprises. The machine is intended to grip the shoe at the right place, apply a layer of polishing wax all around the shoe and perform buffing action to obtain a shiny and assure minimum damage to the shoe. This semi-automatic shoe polishing machine is designed to consist of screw mechanism, a shaft, two bearings, two pulleys, belt, two fibred brushes, an electric motor and springs for gripping the shoe. The developed machine is limited to standard shoe sizes and capable of polishing a pair of shoes in 175 seconds.